An n‐Type to p‐Type Switchable Photoelectrode Assembled from Alternating Exfoliated Titania Nanosheets and Polyaniline Layers. Issue 25 (9th May 2013) - Seger, Brian; McCray, Jonathan; Mukherji, Aniruddh; Zong, Xu; Xing, Zheng; Wang, Lianzhou
<x xml:space="preserve">Abstract</x> Multifunctional nanomaterials: A new type of multilayer thin film containing alternating polyaniline layers and titania nanosheets was self‐assembled (see picture). The film was used as photoelectrode which has n‐type to p‐type switchable semiconducting properties.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>